Enacting Values-Based Change Organization Development in Action (Springer International Publishing, 2018)
This edited volume highlights the use and practice of values in Organization Development (OD). It addresses how those values have changed over time, how they are expressed in OD's approach to consulting, the process of making value-based decisions, and how to deal with value dilemmas and value conflicts. OD scholars and practitioners will learn about the balance of values in practice, particularly as the business outcomes may overtake positive humanistic concerns given intense pressures to enhance organizational productivity year over year. .